Studi kepadatan ikan sidat (Anguilla Spp) di Sungai Tarus Desa Mata Air Kabupaten Kupang pada bulan September sampai Oktober - Kefi, Rudiyanto; Lukas, Ade Yulita Hesti; Santoso, Priyo (Nusa Cendana University, 2024)
The research conducted over approximately 60 days at Tarus River, Mata Air Village, Kupang Regency aimed to assess the variety and abundance of eel fish, a high-value commodity in the international market. The study focused on three stations along the river, where the density of eel fish was observed: station 1 (8 individuals), station 2 (5 individuals), and station 3 (2 individuals). Using digital scales, researchers measured the total weight of the caught fish, alongside noting the types of eel fish obtained. The findings, analyzed descriptively and presented through tables and figures, revealed the prevalence of eel fish type A. marmorata during the research period, primarily in the yellow eel and elver phases with varying sizes. Morphometric measurements indicated that Anguilla marmorata specimens typically ranged in total length (35-47 cm), dorsal length (20-30 cm), anal length (15-25 cm), head diameter (5-7 cm), body diameter (7-9 cm), and total weight (170-181 grams). Additionally, water quality assessments at the research site indicated temperatures ranging from 20-27oC, with a pH of 7.5. Keywords: Identification, eel fish (Anguilla marmorata).